2010
DOI: 10.1308/147870810x12822015504527
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumour presenting with duodenal-jejunal intussusception: a case report

Abstract: Duodenal-jejunal intussusception is an extremely rare occurrence and has never been reported in the context of a gastrointestinal stromal tumour (GIST). We present the case of a duodenal GIST which presented with major intestinal haemorrhage in addition to duodenal-jejunal intussusception. WALL GHALLAB FARMER DURKIN GASTROINTESTINAL STROMAL TUMOUR PRESENTING WITH DUODENAL-JEJUNAL INTUSSUSCEPTION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…negative for malignancy. Wall et al (19) reported the case of a 36-year-old woman with a 15-cm GIST in the second part of the duodenum who underwent pyloruspreserving pancreaticoduodenectomy due to the large size of the tumor and inseparable adhesion to the head of the pancreas. A 91-year-old Japanese woman with a GIST in the third portion of the duodenum received a segmental duodenectomy without reduction of the intussusception but did not undergo a pancreaticoduodenectomy due to her age and performance status (30).…”
Section: Discussionmentioning
confidence: 99%
“…negative for malignancy. Wall et al (19) reported the case of a 36-year-old woman with a 15-cm GIST in the second part of the duodenum who underwent pyloruspreserving pancreaticoduodenectomy due to the large size of the tumor and inseparable adhesion to the head of the pancreas. A 91-year-old Japanese woman with a GIST in the third portion of the duodenum received a segmental duodenectomy without reduction of the intussusception but did not undergo a pancreaticoduodenectomy due to her age and performance status (30).…”
Section: Discussionmentioning
confidence: 99%
“…Together, they are variably prominent components of three syndromes: the familial paraganglioma and gastric GIST syndrome, neurofibromatosis type 1, and the Carney triad (syndrome with paraganglioma-jejunal GIST combination). The two former conditions are inherited as autosomal dominant traits; the later does not appear to be inherited and affects young women predominantly [11].…”
Section: Discussionmentioning
confidence: 99%
“…The endoscopic video capsula plays an important role in the diagnosis of stromal hemorrhagic tumors of the small intestine. It is a simple and harmless examination, that represents at present the examination of first intention in the case of an unexplained digestive haemorrhage after normal oesogastro duodenal endoscopy and an ileo coloscopy 1,2,4,9,10.The endoscopic video capsula made it possible to put the diagnosis of tumors of the small intestine in 8%, 9% of the cases [1,2,9,11,12]. Surgery is the primary treatment of choice and for a long time has been the only effective treatment for GIST with overall 5-year survival rates of 45% -55% until 2001 when Imatinib, a Open Access IJCM Jejunal Stromal Tumor Revealed by a Digestive Hemorrhage Open Access IJCM 487 small molecule inhibiting the kinase activity of c-kit, was recognized to be highly effective in metastasized GIST and revolutionized the treatment of metastasized and/or unresectable GIST [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In the reviewed literature, endoscopic polypectomy was adopted in one patient [18]; however, open surgeries were conducted in all the other patients, including 31 local excisions, 12 segmental duodenectomies with gastroduodenal anastomosis [1,2,38] or duodenojejunal anastomosis [6,9,15,20,23,39,40,42], and four pancreatoduodenectomies [22,24,25,33].…”
Section: Discussionmentioning
confidence: 99%